2018
DOI: 10.1016/j.jbo.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with chondrosarcoma: A survival analysis based on the Surveillance, Epidemiology, and End Results (SEER) database (1973–2012)

Abstract: HighlightsFirst, it is a population-based study which can provide big sample size.Second, similar articles about chondrosarcoma using big data are lacking.Third, the relationship between treatment type and survival outcomes was analyzed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…At present, the role of sex in CS is still controversial. Some previous studies showed that sex was an independent risk factor, while another several studies revealed that sex was not a prognostic factor . In this study, the ratio of male to female patients was ~1.6:1, which was consistent with such ratios in previous studies .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At present, the role of sex in CS is still controversial. Some previous studies showed that sex was an independent risk factor, while another several studies revealed that sex was not a prognostic factor . In this study, the ratio of male to female patients was ~1.6:1, which was consistent with such ratios in previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…Some previous studies showed that sex was an independent risk factor, while another several studies revealed that sex was not a prognostic factor. [21][22][23][24] In this study, the ratio of male to female patients was ~1.6:1, which was consistent with such ratios in previous studies. 23,25 Being female was associated with a better prognosis; thus sex was an independent prognostic factor with obvious effects on OS of patients with pelvic CS.…”
Section: Discussionsupporting
confidence: 91%
“…Older patient age has been associated with poor survival in chondrosarcoma when analyzing large national registries, 17,18 and was the only analyzed factor found to impact survival and disease recurrence in the current study. Although there was no difference in the age of patients in the current series with grade I or II tumors, increasing patient age was associated with increased death due to disease in both patient groups.…”
Section: Discussionmentioning
confidence: 59%
“…17 Three thousand seven hundred thirty seven patients of chondrosarcoma analyzed, showing overall survival rate of 73.9% in five years and patient with distant stage, undifferentiated grade, single radiation have only 30% 5 year survival. 18 A series of 64 patients of localized chondrosarcoma. Thirteen patients had a hemipelvectomy to achieve local tumor control, whereas fifty-one patients underwent a limb-salvage procedure.…”
Section: Seven Patients Withmentioning
confidence: 99%